High magnetic induction 200 μm grade iron-based amorphous soft magnetic alloy strip and preparation method thereof
Through the continuous casting technology and composition design of double-roll thin-band continuous casting technology and composition design, the problems of small size and poor glass formation ability in the existing iron-based amorphous alloy preparation process were solved, and a 200μm-grade iron-based amorphous soft magnetic alloy strip with high magnetic induction and low coercivity were prepared, achieving cost reduction and application expansion.
Patent Information
- Application Number
- CN202211130518.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-09-16
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2042-09-16
AI Technical Summary
The existing iron-based amorphous alloy preparation process has problems such as small size, limited glass formation capacity and high production costs, which limit the development and application of materials.
Using double-roll thin-band continuous casting technology, the 200μm-grade iron-based amorphous soft magnetic alloy strip is prepared by component design and controlling the rolling force between copper rollers. The method includes vacuum induction smelting, constant temperature injection and double rolling to ensure high magnetic induction and low coercivity of the alloy.
The preparation of large-size, high-magnetic inductance iron-based amorphous soft magnetic alloy strips has been realized, with a saturated magnetic induction strength of 1.4T and a coercive force of no more than 9A/m, which reduces production costs and broadens the application range of materials.
Smart Images

Figure CN115482986B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of soft magnetic alloys, and particularly relates to a high magnetic induction 200 μm-level iron-based amorphous soft magnetic alloy strip and a preparation method thereof, which is suitable for preparing large-size iron-based amorphous soft magnetic alloy strips based on a twin-roller thin strip continuous casting technology. Background Art
[0002] Soft magnetic materials are the earliest type of soft magnetic functional materials. With their development, they have experienced pure iron, Permalloy, FeCo alloy, ferrite, oriented / non-oriented silicon steel and amorphous alloys. Silicon steel sheets have a high saturation magnetic induction intensity of up to 2.0T and are currently the most widely used soft magnetic material. However, the large coercive force and high-frequency iron loss of silicon steel inevitably produce huge energy losses in industrial applications. Iron-based amorphous alloys have the characteristics of low coercive force, high magnetic permeability and low iron loss, and the production process is simple, no subsequent processing is required, and the cost advantage is significant. They are considered to be ideal core materials. However, the low saturation magnetic induction intensity and limited strip size of iron-based amorphous alloys severely restrict the development and application of materials.
[0003] In the development of amorphous alloys, the creation of preparation methods and equipment plays a leading role in the development of this field. This is because the success of amorphous alloy preparation depends on the maximum cooling rate of the preparation process and equipment. The critical cooling rate is the best method to describe the glass-forming ability of alloys. Studies have shown that the preparation of iron-based amorphous alloys requires an average cooling rate higher than 10 5 ~10 6 K / s, the heat transfer between the thin strip and the copper roller determines the thickness and amorphous properties of the alloy. To date, many works have been devoted to the research on the preparation methods of iron-based amorphous alloys. However, due to the limitation of glass-forming ability, although many methods for preparing millimeter-scale bulk metallic glass have emerged, including copper mold suction casting, mechanical alloying, die casting, etc., single-roll melt spinning is still the main production method of amorphous strips in recent years. In addition, Albertus et al. produced a 120mm wide NANOMET amorphous ribbon by single-roll melt spinning technology, but its thickness was only 25mm; Wang Anding et al. used the same method to prepare Fe with a thickness of 81μm. 83 C 1 B 11 Si 2 P 3 Amorphous strips; but the width of the strips is only 1 mm. Therefore, in the existing iron-based amorphous alloy system, the lack of preparation methods and the low glass-forming ability of the alloy have severely restricted the preparation and large-scale application of iron-based amorphous alloys.
[0004] Twin-roller thin strip casting technology is a near-net forming technology that has been vigorously advocated by the country since the 21st century. It integrates casting and hot rolling into one step. Due to its short process flow, low cost, and fast cooling speed, it has attracted widespread attention in the traditional silicon steel and non-ferrous metal fields. Compared with the single-roller melt spinning process, the molten metal in this process is subjected to the rolling force generated by two counter-rotating rollers, which promotes heat conduction between the rollers and the alloy melt. In addition, the rolling force accelerates the uniform distribution of elements and inhibits the formation of ordered structures. Therefore, we believe that twin-roller thin strip casting technology is a potential method for the industrial production of large-scale iron-based amorphous alloys. Summary of the invention
[0005] In view of the above-mentioned problems existing in the existing iron-based amorphous alloy preparation process and performance, the purpose of the present invention is to provide a high magnetic induction 200μm grade iron-based amorphous soft magnetic alloy strip and its preparation method, based on the twin-roll thin strip continuous casting technology, through composition design to prepare iron-based amorphous soft magnetic alloy thin strip with excellent performance.
[0006] In order to solve the above technical problems, the technical solution of the present invention is:
[0007] A high magnetic induction 200μm grade iron-based amorphous soft magnetic alloy strip, the chemical expression of the iron-based amorphous alloy is Fe a Ni b P c B d Si e Cu f C g , where a, b, c, d, e, f, and g represent the atomic weight of each component respectively: 67.9≤a≤79.9, 0≤b≤11.9, 10.9≤c≤12.9, 2.9≤d≤5.9, 1.9≤e≤2.9, 0.2≤f≤0.9, 0.05≤g≤0.2, and a+b+c+d+e+f+g=100.
[0008] The method for preparing the high magnetic induction 200 μm-level iron-based amorphous soft magnetic alloy strip comprises the following steps:
[0009] (1) Weighing alloy raw materials according to the atomic percentage specified in the composition design;
[0010] (2) placing the alloy raw material in a vacuum induction melting furnace for melting, evacuating the vacuum and filling it with a protective gas, heating the alloy raw material in step (1) to 1300-1500° C. in a protective gas atmosphere, and melting for 10-30 min;
[0011] (3) evacuating the tundish and heating it to 1200° C., filling it with protective gas, pouring the alloy melt in step (2) into the tundish, and keeping the alloy melt at a constant temperature of 1200° C.;
[0012] (4) The twin-roll mill is evacuated and filled with protective gas. Under the protective gas atmosphere, the alloy melt in the tundish is sprayed at 1200°C between two counter-rotating copper rolls on the twin-roll mill. The rolling force of the rolls is controlled to obtain iron-based amorphous soft magnetic alloy strips of different sizes.
[0013] The method for preparing the high magnetic induction 200 μm grade iron-based amorphous soft magnetic alloy strip, in step (1), the B and P raw materials are boron iron alloy and phosphorus iron alloy respectively, and the purity of the Fe, Ni, Cu, Si, and C raw materials is not less than 99wt%.
[0014] The method for preparing the high magnetic induction 200 μm grade iron-based amorphous soft magnetic alloy strip, in steps (2), (3) and (4), evacuates the air to a pressure of 1×10 -2 Pa or less, the protective gas atmosphere is nitrogen, argon or helium.
[0015] In the method for preparing the high magnetic induction 200 μm-level iron-based amorphous soft magnetic alloy strip, in step (4), the surface linear speed of the copper roller is 0.5 to 2 m / s, and the rolling force between the copper rollers is 10 to 50 kN.
[0016] In the method for preparing the high magnetic induction 200 μm-level iron-based amorphous soft magnetic alloy strip, in step (4), the thickness of the iron-based amorphous soft magnetic alloy strip is 200-300 μm and the width is 20-50 mm.
[0017] The method for preparing the high magnetic induction 200 μm grade iron-based amorphous soft magnetic alloy strip is as follows: after step (4), the iron-based amorphous soft magnetic alloy strip is subjected to annealing heat treatment, the heat treatment temperature is 200-400°C, the holding time is 10-100 minutes, the saturation magnetic induction intensity of the iron-based amorphous soft magnetic alloy strip is not less than 1.4 T, and the coercive force is not greater than 9 A / m.
[0018] The design concept of the present invention is:
[0019] In the present invention, Fe element is a magnetic element, and the addition of Fe element with a high mass fraction helps to improve the saturation magnetic induction intensity of the alloy. However, as the Fe content in the alloy increases, the glass forming ability of the alloy decreases, which is not conducive to the preparation of alloy strips.
[0020] In the present invention, the addition of P element is beneficial to improve the glass forming ability and thermal stability of the alloy. The addition of an appropriate amount of P element can improve the magnetic permeability of the alloy and reduce the coercive force, but as the content of P element increases, the magnetic induction intensity of the alloy will decrease accordingly.
[0021] In the present invention, the addition of element B is mainly to improve the glass forming ability of the alloy and the Curie temperature of the soft magnetic alloy. When the content of element B is low, the expected goal of addition cannot be achieved, while too high a content will reduce the content of ferromagnetic elements in the alloy and deteriorate the soft magnetic properties of the alloy.
[0022] In the present invention, the addition of Si element is mainly to improve the glass forming ability of the alloy and reduce the magnetostriction coefficient of the alloy. When the Si content is too low, it cannot play its role in improving the glass forming ability of the alloy. When the Si content is too high, the saturation magnetic induction intensity of the soft magnetic alloy will be reduced.
[0023] In the present invention, the addition of C element can significantly improve the glass forming ability of the alloy, but excessive addition of C element will increase the room temperature brittleness of the alloy.
[0024] In the present invention, the addition of Cu element can improve the thermal stability of the amorphous alloy, and it is enriched during the annealing process to form scattered Cu clusters, which provide nucleation points for nanocrystalline crystallization. However, if the Cu element content is too high, excessive Cu clusters are easily formed during the strip solidification process, which reduces the glass forming ability of the alloy.
[0025] In the present invention, the addition of Ni element can significantly improve the glass forming ability and bending toughness of Fe-based amorphous alloy. Due to the large negative mixing enthalpy between Ni element and other main alloying elements, the addition of Ni element improves the stability of the alloy's chaos and supercooled liquid phase, thereby improving the glass forming ability of the alloy. With the addition of Ni element, more metal bonds are formed in the amorphous alloy, and these metal bonds are prone to form shear bands under the action of external forces, resulting in shear deformation, thereby improving the toughness of the alloy. Although Ni element is also a magnetic element, due to the smaller magnetic moment, the addition of excessive Ni element will also lead to the degradation of the saturation magnetic induction of the amorphous alloy.
[0026] The advantages and beneficial effects of the present invention are:
[0027] The present invention utilizes a double-roll casting method to control the casting force between copper rollers during the production process, thereby preparing a large-sized, high-magnetic-induction Fe-Ni-PB-Si-C-Cu iron-based amorphous soft magnetic alloy. In this method, by controlling the casting force between the rollers (water-cooled copper rollers), the size and structure of the alloy strip can be effectively controlled, which solves the difficulty of the smaller size of amorphous strips in traditional processes and broadens the application scope and prospects of iron-based amorphous soft magnetic alloy strips. The embodiment of the present invention prepares an iron-based amorphous soft magnetic alloy strip, and XRD analysis proves that it is a completely amorphous structure. The strip thickness can reach 200μm, and the saturation magnetic induction intensity can reach 1.4T. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1Schematic diagram of a vertical twin-roller thin strip casting and rolling mill in an embodiment of the present invention; in the figure: 1. vacuum induction melting furnace; 2. tundish; 3. flow distribution nozzle; 4. water-cooled copper roller; 5. temperature measuring device; 6. amorphous alloy thin strip.
[0029] Figure 2 This is an appearance diagram of the amorphous alloy ribbon prepared in Example 2 of the present invention.
[0030] Figure 3 These are X-ray diffraction patterns of the amorphous alloy ribbons prepared in Examples 1 to 3 of the present invention.
[0031] Figure 4 Graph showing the magnetization curves of the amorphous alloy ribbons prepared in Examples 1 to 3 of the present invention after annealing.
[0032] Figure 5 It is a line graph showing the coercive force variation of the iron-based amorphous soft magnetic alloys prepared in Examples 1 to 3 of the present invention. DETAILED DESCRIPTION
[0033] In the specific implementation process, the present invention designs an iron-based amorphous soft magnetic alloy, whose chemical expression is Fe a Ni b P c B d Si e Cu f C g , a, b, c, d, e, f, and g represent the atomic weight of each component respectively: 67.9≤a≤79.9, 0≤b≤11.9 (preferably 5≤b≤10), 10.9≤c≤12.9, 2.9≤d≤5.9, 1.9≤e≤2.9, 0.2≤f≤0.9, 0.05≤g≤0.2, and a+b+c+d+e+f+g=100.
[0034] like Figure 1 As shown, the vertical twin-roller thin strip casting and rolling mill in the embodiment of the present invention mainly comprises: a vacuum induction melting furnace 1, a tundish 2, a distribution nozzle 3, a water-cooled copper roller 4, and a temperature measuring device 5. The tundish 2 is arranged on one side of the vacuum induction melting furnace 1, and the distribution nozzle 3 is arranged at the bottom of the tundish 2. The lower part of the distribution nozzle 3 corresponds to the gap between two relatively counter-rotating water-cooled copper rollers 4. The alloy melt in the vacuum induction melting furnace 1 is poured into the tundish 2, and the alloy melt forms an amorphous alloy thin strip 6 after passing through the gap between the distribution nozzle 3 and the water-cooled copper roller 4. The temperature measuring device 5 is arranged below the water-cooled copper roller 4.
[0035] Furthermore, the present invention also provides a method for preparing an iron-based amorphous soft magnetic alloy, firstly, the ingredients are prepared and melted according to the alloy composition requirements, and a twin-roll casting and rolling device is used to produce an iron-based amorphous soft magnetic alloy thin strip. During the strip making process, the rolling force between the rollers is controlled to meet the high cooling rate required for the formation of the iron-based amorphous soft magnetic alloy, so as to achieve the preparation of an iron-based amorphous soft magnetic alloy thin strip with a thickness of 200μm. The main steps are as follows:
[0036] (1) Weighing alloy raw materials according to the atomic percentage specified in the composition design;
[0037] (2) After evacuating the vacuum, a protective gas is introduced, and the alloy raw material prepared in step (1) is melted in a vacuum induction melting furnace under the protective gas atmosphere at a melting temperature of 1300 to 1500° C. for a melting time of 10 to 30 min;
[0038] (3) the tundish is evacuated, heated to 1200° C., filled with protective gas, and the alloy melt in step (2) is poured into the tundish;
[0039] (4) In a protective gas atmosphere, the alloy melt in the tundish is sprayed between two counter-rotating copper rollers at 1200°C, and the rolling force of the rollers is controlled to obtain iron-based amorphous soft magnetic alloy strips of different sizes.
[0040] In order to further understand the present invention, the iron-based amorphous soft magnetic alloy and its preparation process in the present invention are described in combination with the following specific embodiments. These embodiments are only used to illustrate the present invention, and this application is not limited to these embodiments.
[0041] Example 1
[0042] In this embodiment, the atomic percentage chemical formula of the iron-based amorphous soft magnetic alloy is Fe 71 Ni 9 P 11.9 B 4.9 Si 2.5 Cu 0.6 C 0.1 , and its specific preparation method is as follows:
[0043] (1) Selection of alloy raw materials: Fe 71 Ni 9 P 11.9 B 4.9 Si 2.5 Cu 0.6 C 0.1 Convert atomic percentage in chemical formula to mass percentage Fe 78.89 Ni 10.54 P 7.26 B 1.17 Si 1.33 Cu 0.8 C0.01 , Fe rods (purity 99.95wt%), Ni plates (purity 99.96wt%), Si sheets (purity 99.99wt%), Cu foils (purity 99.95wt%), C powders (purity 99.99wt%), ferroboron alloys (containing 19.35wt% boron) and ferrophosphorus alloys (containing 25.23% phosphorus) were weighed by mass percentage, and the mass of the alloy raw materials was 3 to 5Kg.
[0044] (2) Master alloy smelting: The alloy raw materials prepared in step (1) are placed in a graphite crucible of a vacuum induction melting furnace, and the furnace is evacuated to a pressure of 1×10 -2 Pa, fill with argon (volume purity 99.999%) for protection, and when the pressure in the vacuum induction melting furnace is 0.01MPa higher than the atmospheric pressure, close the air inlet valve. Induction heating melts the alloy raw materials, the melting temperature is 1300℃~1400℃, and after the alloy raw materials are completely melted, continue melting for 3min, the total melting time is 10~20min, and electromagnetic stirring during the melting process ensures that the chemical elements in the alloy melt are evenly distributed.
[0045] (3) Transfer of alloy melt: The tundish is evacuated to a vacuum pressure of 1×10 -2 Pa, set a step-by-step temperature program, preheat the tundish to 1200°C, fill it with argon (volume purity 99.99%) for protection, and stop filling the tundish after the pressure in the tundish reaches the standard atmospheric pressure. Under completely sealed conditions, pour the molten liquid metal in step (2) into the tundish, and keep the alloy melt at a constant temperature of 1200°C in the tundish. During the constant temperature process, the alloy melt flows to the water outlet.
[0046] (4) Preparation of amorphous alloy thin strips: The vertical twin-roll mill was evacuated to a pressure of 1×10 -2 After the alloy melt is kept constant temperature in the tundish in step (3), the graphite plug rod is pulled out, and the molten alloy is sprayed into the space between two water-cooled copper rolls rotating in opposite directions at a surface linear velocity of 1 m / s by the weight of the alloy. The casting force between the rolls is controlled to be 20 kN, and the amorphous alloy strip is obtained with a width of about 20 mm and a thickness of about 280 μm.
[0047] (5) Characterization of alloy structure: X-ray diffractometer is used to detect the structure of the prepared iron-based amorphous soft magnetic alloy, so as to identify the microstructure state of the alloy. The detection angle range of the X-ray instrument is 30° to 90°, and the scanning speed is 3° / min. Figure 3 As shown in the X-ray diffraction image of the prepared amorphous alloy ribbon, the amorphous ribbon has only a diffusely distributed bun peak at 45°, and no other obvious Bragg diffraction peaks exist, indicating that the alloy is in a completely amorphous state.
[0048] (6) Annealing heat treatment: The amorphous alloy thin strip is placed in a tube furnace for annealing heat treatment. The tube furnace is heated to 300°C in advance. After reaching the set temperature, the strip is placed in the tube furnace and kept warm for 10 minutes. After the constant temperature is over, the strip is taken out and air-cooled to room temperature. Annealing at the crystallization temperature eliminates the residual internal stress in the strip, which is beneficial to improving the soft magnetic properties of the iron-based amorphous strip.
[0049] (7) Magnetic property test: The saturation magnetic induction intensity and coercive force of the annealed Fe-based amorphous alloy thin strip were tested using a vibration test magnetometer and a hysteresis loop instrument, respectively. The maximum field strengths applied in the tests were 800KA / m and 800A / m, respectively.
[0050] (8) See Figure 4 , the magnetization curve of the iron-based amorphous soft magnetic alloy prepared in this embodiment. Figure 5 , the coercivity curve of the alloy prepared in this embodiment varies with the casting force. The results show that the iron-based amorphous soft magnetic alloy Fe prepared in this embodiment 71 Ni 9 P 11.9 B 4.9 Si 2.5 Cu 0.6 C 0.1 The saturation magnetic induction density and coercive force are 1.41T and 6.3A / m respectively.
[0051] Example 2
[0052] In this embodiment, the atomic percentage chemical formula of the iron-based amorphous soft magnetic alloy is Fe 71 Ni 9 P 11.9 B 4.9 Si 2.5 Cu 0.6 C 0.1 , and its specific preparation method is as follows:
[0053] (1) Selection of alloy raw materials: Fe 71 Ni 9 P 11.9 B 4.9 Si 2.5 Cu 0.6 C 0.1 Convert atomic percentage in chemical formula to mass percentage Fe 78.89 Ni 10.54 P 7.26 B 1.17 Si 1.33 Cu 0.8 C 0.01, Fe rods (purity 99.95wt%), Ni plates (purity 99.96wt%), Si sheets (purity 99.99wt%), Cu foils (purity 99.95wt%), C powders (purity 99.99wt%), ferroboron alloys (containing 19.35wt% boron) and ferrophosphorus alloys (containing 25.23% phosphorus) were weighed by mass percentage, and the mass of the alloy raw materials was 3 to 5Kg.
[0054] (2) Master alloy smelting: The alloy raw materials prepared in step (1) are placed in a graphite crucible of a vacuum induction melting furnace, and the furnace is evacuated to a pressure of 1×10 -2 Pa, fill with argon (volume purity 99.999%) for protection, and when the pressure in the vacuum induction melting furnace is 0.01MPa higher than the atmospheric pressure, close the air inlet valve. Induction heating melts the alloy raw materials, the melting temperature is 1300℃~1400℃, and after the alloy raw materials are completely melted, continue melting for 3min, the total melting time is 10~20min, and electromagnetic stirring during the melting process ensures that the chemical elements in the alloy melt are evenly distributed.
[0055] (3) Transfer of alloy melt: The tundish is evacuated to a vacuum pressure of 1×10 -2 Pa, set a step-by-step temperature program, preheat the tundish to 1200°C, fill it with argon (volume purity 99.99%) for protection, and stop filling the tundish after the pressure in the tundish reaches the standard atmospheric pressure. Under completely sealed conditions, pour the molten liquid metal in step (2) into the tundish, and keep the alloy melt at a constant temperature of 1200°C in the tundish. During the constant temperature process, the alloy melt flows to the water outlet.
[0056] (4) Preparation of amorphous alloy thin strips: The vertical twin-roll mill was evacuated to a pressure of 1×10 -2 After the alloy melt is kept constant temperature in the tundish in step (3), the graphite plug rod is pulled out, and the molten alloy is sprayed into the space between two water-cooled copper rolls rotating in opposite directions at a surface linear velocity of 1 m / s by the weight of the alloy. The casting force between the rolls is controlled to be 30 kN, and the amorphous alloy thin strip is obtained with a width of about 30 mm and a thickness of about 260 μm. Figure 2 .
[0057] (5) Characterization of alloy structure: X-ray diffractometer is used to detect the structure of the prepared iron-based amorphous soft magnetic alloy, so as to identify the microstructure state of the alloy. The detection angle range of the X-ray instrument is 30° to 90°, and the scanning speed is 3° / min. Figure 3 As shown in the X-ray diffraction image of the prepared amorphous alloy ribbon, the amorphous ribbon has only a diffusely distributed bun peak at 45°, and no other obvious Bragg diffraction peaks exist, indicating that the alloy is in a completely amorphous state.
[0058] (6) Annealing heat treatment: The amorphous alloy thin strip is placed in a tube furnace for annealing heat treatment. The tube furnace is heated to 300°C in advance. After reaching the set temperature, the strip is placed in the tube furnace and kept warm for 10 minutes. After the constant temperature is over, the strip is taken out and air-cooled to room temperature. Annealing at the crystallization temperature eliminates the residual internal stress in the strip, which is beneficial to improving the soft magnetic properties of the iron-based amorphous strip.
[0059] (7) Magnetic property test: The saturation magnetic induction intensity and coercive force of the annealed Fe-based amorphous alloy thin strip were tested using a vibration test magnetometer and a hysteresis loop instrument, respectively. The maximum field strengths applied in the tests were 800KA / m and 800A / m, respectively.
[0060] (8) See Figure 4 , the magnetization curve of the iron-based amorphous soft magnetic alloy prepared in this embodiment. Figure 5 , the coercivity curve of the alloy prepared in this embodiment varies with the casting force. The results show that the iron-based amorphous soft magnetic alloy Fe prepared in this embodiment 71 Ni 9 P 11.9 B 4.9 Si 2.5 Cu 0.6 C 0.1 The saturation magnetic induction density and coercive force are 1.42T and 7.4A / m respectively.
[0061] Example 3
[0062] In this embodiment, the atomic percentage chemical formula of the iron-based amorphous soft magnetic alloy is Fe 71 Ni 9 P 11.9 B 4.9 Si 2.5 Cu 0.6 C 0.1 , and its specific preparation method is as follows:
[0063] (1) Selection of alloy raw materials: Fe 71 Ni 9 P 11.9 B 4.9 Si 2.5 Cu 0.6 C 0.1 Convert atomic percentage in chemical formula to mass percentage Fe 78.89 Ni 10.54 P 7.26 B 1.17 Si 1.33 Cu 0.8 C 0.01, Fe rods (purity 99.95wt%), Ni plates (purity 99.96wt%), Si sheets (purity 99.99wt%), Cu foils (purity 99.95wt%), C powders (purity 99.99wt%), ferroboron alloys (containing 19.35wt% boron) and ferrophosphorus alloys (containing 25.23% phosphorus) were weighed by mass percentage, and the mass of the alloy raw materials was 3 to 5Kg.
[0064] (2) Master alloy smelting: The alloy raw materials prepared in step (1) are placed in a graphite crucible of a vacuum induction melting furnace, and the furnace is evacuated to a pressure of 1×10 -2 Pa, fill with argon (volume purity 99.999%) for protection, and when the pressure in the vacuum induction melting furnace is 0.01MPa higher than the atmospheric pressure, close the air inlet valve. Induction heating melts the alloy raw materials, the melting temperature is 1300℃~1400℃, and after the alloy raw materials are completely melted, continue melting for 3min, the total melting time is 10~20min, and electromagnetic stirring during the melting process ensures that the chemical elements in the alloy melt are evenly distributed.
[0065] (3) Transfer of alloy melt: The tundish is evacuated to a vacuum pressure of 1×10 -2 Pa, set a step-by-step temperature program, preheat the tundish to 1200°C, fill it with argon (volume purity 99.99%) for protection, and stop filling the tundish after the pressure in the tundish reaches the standard atmospheric pressure. Under completely sealed conditions, pour the molten liquid metal in step (2) into the tundish, and keep the alloy melt at a constant temperature of 1200°C in the tundish. During the constant temperature process, the alloy melt flows to the water outlet.
[0066] (4) Preparation of amorphous alloy thin strips: The vertical twin-roll mill was evacuated to a pressure of 1×10 -2 After the alloy melt is kept constant temperature in the tundish in step (3), the graphite plug rod is pulled out, and the molten alloy is sprayed into the space between two water-cooled copper rolls rotating in opposite directions at a surface linear velocity of 1 m / s by the weight of the alloy. The casting force between the rolls is controlled to be 40 kN, and the amorphous alloy strip is obtained with a width of about 40 mm and a thickness of about 220 μm.
[0067] (5) Characterization of alloy structure: X-ray diffractometer is used to detect the structure of the prepared iron-based amorphous soft magnetic alloy, so as to identify the microstructure state of the alloy. The detection angle range of the X-ray instrument is 30° to 90°, and the scanning speed is 3° / min. Figure 3 As shown in the X-ray diffraction image of the prepared amorphous alloy ribbon, the amorphous ribbon has only a diffusely distributed bun peak at 45°, and no other obvious Bragg diffraction peaks exist, indicating that the alloy is in a completely amorphous state.
[0068] (6) Annealing heat treatment: The amorphous alloy thin strip is placed in a tube furnace for annealing heat treatment. The tube furnace is heated to 300°C in advance. After reaching the set temperature, the strip is placed in the tube furnace and kept warm for 10 minutes. After the constant temperature is over, the strip is taken out and air-cooled to room temperature. Annealing at the crystallization temperature eliminates the residual internal stress in the strip, which is beneficial to improving the soft magnetic properties of the iron-based amorphous strip.
[0069] (7) Magnetic property test: The saturation magnetic induction intensity and coercive force of the annealed Fe-based amorphous alloy thin strip were tested using a vibration test magnetometer and a hysteresis loop instrument, respectively. The maximum field strengths applied in the tests were 800KA / m and 800A / m, respectively.
[0070] (8) See Figure 4 , the magnetization curve of the iron-based amorphous soft magnetic alloy prepared in this embodiment. Figure 5 , the coercivity curve of the alloy prepared in this embodiment varies with the casting force. The results show that the iron-based amorphous soft magnetic alloy Fe prepared in this embodiment 71 Ni 9 P 11.9 B 4.9 Si 2.5 Cu 0.6 C 0.1 The saturation magnetic induction density and coercive force are 1.4T and 8.8A / m respectively.
[0071] The implementation results show that the present invention has the advantages of short process, low cost and large strip size, and is expected to replace the existing single-roll melt spinning process and be widely used in the preparation of iron-based amorphous alloy thin strips.
Claims
1. A high magnetic induction 200 μm grade iron-based amorphous soft magnetic alloy strip, characterized in that: The atomic percentage chemical formula of iron-based amorphous soft magnetic alloy is Fe 71 Ni9P 11.9 B 4.9 Si 2.5 Cu 0.6 C 0.1 ; The method for preparing the high magnetic induction 200 μm-level iron-based amorphous soft magnetic alloy strip comprises the following steps: (1) Weighing alloy raw materials according to the atomic percentage specified in the composition design; (2) placing the alloy raw material in a vacuum induction melting furnace for melting, evacuating the vacuum and filling it with a protective gas, heating the alloy raw material in step (1) to 1300-1500° C. in a protective gas atmosphere, and melting for 10-30 min; (3) evacuating the tundish and heating it to 1200° C., filling it with protective gas, pouring the alloy melt in step (2) into the tundish, and keeping the alloy melt at a constant temperature of 1200° C.; (4) The twin-roll mill is evacuated and filled with protective gas. Under the protective gas atmosphere, the alloy melt in the tundish is sprayed at 1200°C between two counter-rotating copper rolls on the twin-roll mill. The rolling force of the rolls is controlled to obtain iron-based amorphous soft magnetic alloy strips of different sizes.
2. The method for preparing a high magnetic induction 200 μm-level iron-based amorphous soft magnetic alloy strip according to claim 1, characterized in that: The following steps are involved: (1) Weighing alloy raw materials according to the atomic percentage specified in the composition design; (2) placing the alloy raw material in a vacuum induction melting furnace for melting, evacuating the vacuum and filling it with a protective gas, heating the alloy raw material in step (1) to 1300-1500° C. in a protective gas atmosphere, and melting for 10-30 min; (3) evacuating the tundish and heating it to 1200° C., filling it with protective gas, pouring the alloy melt in step (2) into the tundish, and keeping the alloy melt at a constant temperature of 1200° C.; (4) The twin-roll mill is evacuated and filled with protective gas. Under the protective gas atmosphere, the alloy melt in the tundish is sprayed at 1200°C between two counter-rotating copper rolls on the twin-roll mill. The rolling force of the rolls is controlled to obtain iron-based amorphous soft magnetic alloy strips of different sizes.
3. The method for preparing the high magnetic induction 200 μm grade iron-based amorphous soft magnetic alloy strip according to claim 2, characterized in that: In step (1), the B and P raw materials are ferroboron alloy and ferrophosphorus alloy respectively, and the purity of the Fe, Ni, Cu, Si and C raw materials is not less than 99wt%.
4. The method for preparing a high magnetic induction 200 μm-level iron-based amorphous soft magnetic alloy strip according to claim 2, characterized in that: In steps (2), (3) and (4), the vacuum is evacuated to a pressure of 1×10 -2 Pa or less, the protective gas atmosphere is nitrogen, argon or helium.
5. The method for preparing a high magnetic induction 200 μm-level iron-based amorphous soft magnetic alloy strip according to claim 2, characterized in that: In step (4), the surface linear velocity of the copper roller is 0.5 to 2 m / s, and the rolling force between the copper rollers is 10 to 50 kN.
6. The method for preparing a high magnetic induction 200 μm grade iron-based amorphous soft magnetic alloy strip according to claim 2, characterized in that: In step (4), the thickness of the iron-based amorphous soft magnetic alloy strip is 200-300 μm and the width is 20-50 mm.
7. The method for preparing a high magnetic induction 200 μm-level iron-based amorphous soft magnetic alloy strip according to claim 2, characterized in that: After step (4), the iron-based amorphous soft magnetic alloy strip is subjected to annealing heat treatment at a heat treatment temperature of 200-400°C for a holding time of 10-100 min. The saturation magnetic induction intensity of the iron-based amorphous soft magnetic alloy strip is not less than 1.4 T, and the coercive force is not greater than 9 A / m.
Citation Information
Patent Citations
Continuous preparation method for iron base amorphous strips
CN109825781A
ALLOY COMPOSITION, Fe-BASED NANOCRYSTALLINE ALLOY AND METHOD FOR PRODUCING THE SAME, AND MAGNETIC PART
JP2013185162A